Improving the Quality of Baby Sleep by Giving Massages Aged 0-6 Months at Muhammadiyah Semampir Branch Office in Surabaya - Pipit Festy Wiliarnarti; Yuanita Wulandari; Nur Aini (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Sleep is one of the basic human needs. The need for sleep for all ages differs. Sleep disorders can occur in children with manifestations of difficulty in starting to sleep and maintaining sleep. One way to overcome baby sleep disorders is with Massage (touch). Touching the baby's skin will stimulate blood circulation and add more oxygen wave energy to the brain, improving the circulation and respiration systems. The feeling of comfort and relaxation from massage will enhance sleep quality in infants aged 0-6 months. This baby massage stimulates the nervous and respiratory systems and smooths blood circulation. Massage can stimulate hormones, affecting the body's work systems, such as sleep patterns, and can help babies with difficulty sleeping soundly. This Community Service aims to show that baby massage can improve sleep quality in infants aged 0-6 months. The method used in community service was to massage babies aged 0-6 months for two weeks. The massage was carried out continuously and continued independently by mothers at home to improve sleep quality in infants aged 0-6 months. Results obtained after massage on babies aged 0-3 months for two weeks showed that the average sleep time of babies increased by 96 minutes, while the average sleep time of babies aged 4-6 months was 115 minutes. It shows that baby massage dramatically influences the quality of baby sleep. Conclusion: This baby massage is an effort made to improve the quality of baby sleep because it is essential for their growth and development.